A Systematic Literature Review of Six Sigma Implementation’s Benefit to the Organization - Adi Permana; Edward Steven; Humiras Hardi Purba (Spektrum Industri, 2021)
Six sigma is a methodology which started in manufacturing sector that focuses in reducing the product variation, reducing defect and increasing customer satisfaction. Six sigma is being popular and being adopted in many organizations across the industries as well as the organization sizes around the globe. Six sigma successfully delivered many benefits starting from the quality improvement, increase productivity, increase job satisfaction, deliver cost saving, improve on time delivery and improve customer satisfaction that leads to more business growth, more profit and building the great foundation for the business sustainability